Factors Driving Jute to Maize Shift in Uttar Dinajpur, West Bengal (Indian Journal of Extension Education, 2023)
Jute is an important crop that contributes a pivotal role in the economy and supports the livelihoods of the farmers of the Northern part of West Bengal. However, farmers in the region are gradually shifting away from traditional jute cultivation to adopting maize as their preference and the study investigated the factors influencing transformation. Responses were collected from 60 farmers of Chopra Block using a structured interview schedule during the peak season of maize cultivation in 2019. Principal Component Analysis was used to extract significant factors explaining the motives behind farmers’ preference for maize over jute crops. The study envisages that the factors including lack of capital, remunerative market price, high labor costs, poor soil quality and inadequate irrigation water, unavailability of improved seed varieties, high input costs, and inadequate market facilities are the key factors for discouragement of cultivation of jute. The government should develop some supportive infrastructure like providing high-quality maize seeds, conducting awareness programs to educate the farmers about the benefits and byproducts of maize, and offering knowledge about export and import markets. Capacity building and extension approaches can aid the transition and foster positive contributions to the agricultural sector of the locality.